MHD free convection with Joule heating and entropy generation inside an H-shaped hollow structure - Md. Hasibul Islam; Riyan Hashem Jamy; Md. Shahneoug Shuvo; Sumon Saha (Heliyon, 2024)
In this research, a free convective flow of water inside an H-shaped hollow structure which is subjected to the existence of an exterior magnetic field and Joule heating is computationally investigated. The structure's right and left upright surfaces are maintained at invariant ambient thermal condition, while the top and bottom-most surfaces of the structure are in adiabatic condition. The rest of the inner walls are heated isothermally. Computational analysis is carried out for different configurations of the chamber by solving Navier-Stokes and heat energy equations via the finite element approach. Parametric computations are conducted by varying Hartmann numbers (0 ≤ Ha ≤ 20), Rayleigh numbers (103 ≤ Ra ≤ 106), width of the vertical sections (0.2 ≤ d/L ≤ 0.4, where L denotes the structure's reference dimension), and thickness of the horizontal middle section (0.2 ≤ t/L ≤ 0.4). To find out the impact of the governing parameters on thermal performance for different configurations, the mean Nusselt number along the hot walls, mean temperature of fluid, overall entropy generation, and thermal performance criterion are assessed. In addition, the variations in fluid motion and thermal patterns are reported in terms of streamlines, isotherms, and heatlines. With a larger mean Nusselt number and smaller thermal performance criterion, better heat transmission performance is found for thicker horizontal middle section and wider vertical sections. The maximum reduction in thermal performance criterion is found to be 87.8 % for increasing the width of the vertical sections. However, in the cases of Ha and d/L, there is an interesting transition in Nusselt number noticed for different Rayleigh numbers.